2013
DOI: 10.2220/biomedres.34.105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated milnacipran and fluvoxamine treatment on mechanical allodynia in a mouse paclitaxel-induced neuropathic pain model

Abstract: Paclitaxel is widely used in cancer chemotherapy for the treatment of solid tumors, but it frequently causes peripheral neuropathy. Milnacipran, a serotonin/noradrenaline reuptake inhibitor and fluvoxamine, a selective serotonin reuptake inhibitor, have shown efficacy against several chronic pain syndromes. In this study, we investigated the attenuation of paclitaxel-induced mechanical allodynia in mice by milnacipran and fluvoxamine. Paclitaxel was administered once per day (2 mg/kg, intraperitoneally (i.p.))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Previous observations have shown that chronic elevation of 5-HT levels can increase response thresholds in rodent models of mechanical allodynia [35][37]. Our result extends this observation by showing that a similar effect can be reversibly induced on a faster timescale in non-pathological conditions by recruiting DRN 5-HT neurons.…”
Section: Discussionsupporting
confidence: 88%
“…Previous observations have shown that chronic elevation of 5-HT levels can increase response thresholds in rodent models of mechanical allodynia [35][37]. Our result extends this observation by showing that a similar effect can be reversibly induced on a faster timescale in non-pathological conditions by recruiting DRN 5-HT neurons.…”
Section: Discussionsupporting
confidence: 88%
“…The SNRI milnacipran inhibited neuropathic pain by blocking noradrenaline and serotonin reuptake. 14,33) Sciatic nerve ligation in mice induces pain behavior and is used as a model of neuropathic pain. The pain behavior in these mice was not affected by a single injection of milnacipran s.c. but was significantly suppressed by repeated milnacipran injections.…”
Section: Fig 3 Effect Of An Antiarrhythmic Drug On the Mechanical Amentioning
confidence: 99%
“…In rodent models of CIPN increased sensitivity to a mechanical stimulus (mechanical allodynia) is commonly used as a read out for pain [7; 13; 16; 27; 34; 46]. Paclitaxel stabilizes microtubules thereby inhibiting with cell division [35].…”
Section: Introductionmentioning
confidence: 99%